TRANSFORMASI DIGITAL PENDAFTARAN TANAH: TANTANGAN DAN EFEKTIVITAS IMPLEMENTASI APLIKASI SENTUH TANAHKU DALAM ERA SOCIETY 5.0 - Rana Tatsbita Noer; Salvia Salsabila; Aprila Niravita; Muhammad Adymas Hikal Fikri; Harry Nugroho (JURNAL ILMIAH NUSANTARA, 2024)
Digital transformation of land registration is an important step in improving efficiency and transparency in land asset management. This research analyzes the challenges and effectiveness of implementing the “sentuh tanahku” application in the context of Society 5.0, where technology plays a crucial role in improving social interaction and public services. The research method used includes qualitative analysis through interviews with users and application managers, as well as literature study. The results show that although the application is able to speed up the registration process and reduce bureaucracy, challenges such as the lack of digital literacy among the community and uneven technological infrastructure are still significant obstacles. However, the app's effectiveness in providing better access to information and simplifying land transactions is expected to support the realization of Society 5.0 which focuses on collaboration between humans and technology. This research includes discussions on improving digital training for users and strengthening infrastructure to support the sustainability of this transformation.